Corrosion Monitoring with Tangential Radiography and Limited View Computed Tomography - Ewert,U; Tschaikner,M; Hohendorf,S; Bellon,C; Haith,MI; Huthwaite,P; Lowe,MJS (American Institute of Physics (AIP), 2015)
Accurate and reliable detection of subsea pipeline corrosion is required in order to verify the integrity of the pipeline. A laboratory trial was conducted with a representative pipe sample. The accurate measurement of the wall thickness and corrosion was performed with high energy X-rays and a digital detector array. A 7.5 MV betatron was used to penetrate a stepped pipe and a welded test pipe of 3m length and 327mm outer diameter, with different artificial corrosion areas in the 24mm thick steel wall. The radiographs were taken with a 40 x 40cm² digital detector array, which was not large enough to cover the complete pipe diameter after magnification. A C-arm based geometry was tested to evaluate the potential for automated inspection in field. The primary goal was the accurate measurement of wall thickness conforming to the standard. The same geometry was used to explore the ability of a C-arm based scanner in asymmetric mode for computed tomography (CT) measurement, taking projections covering only two thirds of the pipe diameter. The technique was optimized with the modelling software aRTist. A full volume of the pipe was reconstructed and the CT data set was used for reverse engineering, providing a CAD file for further aRTist simulations to explore the technique for subsea inspections.